2011
DOI: 10.1039/c1mb05189j
|View full text |Cite
|
Sign up to set email alerts
|

PELDOR analysis of enzyme-induced structural changes in damaged DNA duplexes

Abstract: PELDOR (pulsed electron-electron double resonance) spectroscopy was applied to determine spin-spin distances in spin-labeled DNA duplexes (13-mer and 17-mer) containing the damaged sites 8-oxoguanine or uncleavable abasic site analogue tetrahydrofuran. The lesions were located in one strand of the DNA, and two nitroxyl spin labels were attached at the 5'- and 3'-ends of the complementary strand. PELDOR data allow us to obtain distances between the two spin labels in DNAs, which turned out to be around 5 nm for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 77 publications
2
14
0
Order By: Relevance
“…One can see that the positions of the main maximum of all DNA duplexes in the free state are close to 5.0 nm (Table 2 ) and are in line with the previously obtained data for undamaged DNA ( 49 ). A comparison of distances in the APE1–DNA complexes revealed that under these experimental conditions, DNA duplexes partially remain in a free state with a distance of ∼5.0 nm, along with emergence of a substantial amount of conformations with smaller distances.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…One can see that the positions of the main maximum of all DNA duplexes in the free state are close to 5.0 nm (Table 2 ) and are in line with the previously obtained data for undamaged DNA ( 49 ). A comparison of distances in the APE1–DNA complexes revealed that under these experimental conditions, DNA duplexes partially remain in a free state with a distance of ∼5.0 nm, along with emergence of a substantial amount of conformations with smaller distances.…”
Section: Resultssupporting
confidence: 91%
“…Conventional EPR spectra and original PELDOR time traces of the analysed systems were similar to those presented previously ( 36 , 49 ). The PELDOR traces contain a contribution from inter-molecular magnetic dipole–dipole interactions between spin labels of different DNA molecules and a contribution from intra-molecular interactions between two spin labels in the same DNA molecule.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…It has been previously shown by pre–steady-state analyses that the recognition of a damaged nucleotide in a duplex substrate is accompanied by a conformational adjustment of the damaged DNA; this process optimizes specific contacts in the enzyme–substrate complex in the case of either Fpg ( Kuznetsov et al, 2007b , 2011 , 2012 ) or OGG1 ( Kuznetsov et al, 2007a , 2014 ; Kuznetsova et al, 2014 ; Lukina et al, 2017 ). The results of the kinetic analysis clearly indicated that Fpg and OGG1 can control substrate specificity via a multi-stage mechanism of recognition of a specific site, accompanied by conformational changes both in the DNA substrate and in the enzyme.…”
Section: Resultsmentioning
confidence: 99%